EVALUASI KEBIJAKAN REVITALISASI BANGUNAN CAGAR BUDAYA BENTENG WILLEM II UNGARAN KABUPATEN SEMARANG - Wijanarko .; Puji Astuti; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
Cultural heritage is an invaluable legacy for the region. Willem II Ungaran Fortress is a regional cultural heritage that can make an identity Ungaran preservation Semarang District as an area of cultural heritage and regional assets. The need for conservation with the maintenance and care by the local government got a problem regarding the ownership of the building. Then the revitalization effort has failed. The need for evaluation to measure the starting shortcomings in the implementation of a heritage revitalization. The method used in this research is the Qualitative Research Methods that use descriptive analytical research type. Object of this study is Semarang Regency / City Ungaran related benchmarks / evaluations Fort Willem II Ungaran in revitalization efforts by the District Government of Semarang.